2015
DOI: 10.1177/1538574415602780
|View full text |Cite
|
Sign up to set email alerts
|

Open Versus Endovascular Repair of Inflammatory Abdominal Aortic Aneurysms

Abstract: Endovascular aneurysm repair of IAAAs is associated with decreased procedure duration, transfusion needs, hospitalization, and morbidity compared to OSR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…14 As EVAR is a less invasive technique than OSR, some authors have demonstrated that it is associated to fewer blood transfusions and shorter hospital stay. 6 However, we did not find any differences in our series.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…14 As EVAR is a less invasive technique than OSR, some authors have demonstrated that it is associated to fewer blood transfusions and shorter hospital stay. 6 However, we did not find any differences in our series.…”
Section: Discussioncontrasting
confidence: 70%
“…Some previous reports have suggested EVAR as a less invasive treatment for inflammatory aneurysms with less morbidity and mortality. 2,6 The aim of this study is to describe our postoperative and long-term institutional outcomes in the treatment of IAAA with both, open surgery and endovascular repair over a 15-year period.…”
Section: Introductionmentioning
confidence: 99%
“…14,17 These findings were in accordance with abdominal aortic aneurysms treated with OS or ET. 33,34…”
Section: Discussionmentioning
confidence: 99%
“…Overall mortality was 14% (OR) vs. 2% (EVAR). Another analysis concerning inflammatory AAA concluded that EVAR is associated with shorter surgery duration, lower need for transfusion and lower morbidity compared to OR [112]. Nonetheless, there is no evidence-based proof that EVAR or OR should be preferred in inflammatory AAA.…”
Section: Inflammatory Aneurysmsmentioning
confidence: 99%